From a demographic dividend to sustainable development of PRC with ageing population: view of Chinese experts - M. D. Volkova; M. S. Kruglova (Russian Journal of Economics and Law)
Objective: to identify the main trends in the studies of the PRC demographic problems by Chinese researchers; to determine the main directions of developments within the concept of demographic dividend in terms of their main problems and prospects for further adjustments in accordance with the ever-changing state demographic policy and the goals of sustainable development.   Methods: qualitative methods (comparative analysis, generalization) of a systematic review of empirical studies.   Results: the main trends and directions of modern Chinese demographic research are highlighted, one of which is the study of demographic processes as an important factor in the development of further trajectory of the PRC sustainable development. It is concluded that Chinese authors often write about the aging population as a competitive advantage of China. They explainthat with a competent economic and demographic policy, the “silver generation” will become an active participant in the economic and production activities of the country, making a noticeable contribution to GDP. We also analyze alternative approaches to the concept of demographic dividend, in which the main factor of China’s economic growth is determined notas the quantity but as the quality of labor force.   Scientific novelty: the article systematizes the works by Chinese researchers in the context of the demographic dividend and identifies their main problems and focuses.   Practical significance: the main conclusions of the article can be used in scientific and pedagogical activities in the study of economic and demographic policy of China. The research results can also be studied to clarify the demographic policy of the Russian Federation.